PWE-231 Split stomas, intestinal failure and outcomes after emergency laparotomy. (22nd June 2015) - Kalaiselvan, R; Tamura, C; Smith, D; Walsh, CJ
Abstract : Introduction: Intestinal anastomoses are regarded as high risk in the context of emergency laparotomy (EL) for abdominal catastrophe in critically ill patients. Resection and split stoma formation may be a better option yet surgeons may be intimidated by formation of proximal stomas and the associated Intestinal Failure (IF) that ensues. We have audited our outcomes of emergency bowel resection with split stomas (SS) and their reversal. Method: Retrospective study of consecutive patients who underwent EL and formation of SS from July 2010 to April 2014. Outcome analysis was done from prospectively maintained nutrition team database and cross-referenced with case notes. Data are represented as median (range). Emergency non-split stomas excluded. Results: 27 patients (13 men; age 68(36–90)years) underwent EL following de novo acute intra-abdominal catastrophe (n = 24) or as a post-operative complication following elective surgery (n = 3). Aetiology was acute mesenteric ischaemia (n = 13), intestinal obstruction (n = 8), peritionitis due to perforation (n = 3) and post-operative complications (peritonitis, n = 3). Median ASA was 3(1–4). The length of hospital stay was a median of 92(29–218) days. 3 patients died at 28, 29 and 87 days following resuscitative laparotomy yielding a 30-day mortality of 6.3%(n = 2) and 90 day mortality of 9.3%(n = 3). All patients required parenteral nutrition (PN). PN was delivered by peripherally inserted central catheter in all patients. Median duration of PN was 94(26–322) days. 2 patients achieved nutritional autonomy and elected to live with their stoma. 22(81%) of the original 27 patients underwent stoma reversal at a median of 3.7(1.6–14.3) months following the initial insult. 17 patients required in-patient PN because of problematic high output. After reversal of their stomas they became nutritionally independent. The remaining 5 patients required PN for 74(30–137) days after the EL and were nutritionally optimised on oral diet on discharge. These 5 patients returned electively for successful stoma reversal. There were no anastomotic or intra abdominal septic complications. There was 1(3.8%) post op death after stoma reversal (myocardial infarction). No patient developed Type 3 IF. Survival following EL at 1 year and 3 years was 81% and 70% respectively. Survival following reversal of stoma (n = 22) at 1 year and 4 years was 95% and 73% at a median follow-up of 25(5–39) months. Comparison of overall survival was not significantly different when comparing age range 36–69 yrs (n = 12, 1yr -83%, 4yrs – 75%) and age range 70–90 yrs (n = 15, 1yr – 80%, 4 yrs 60%) (P = 0.4 - Fisher's exact test). Conclusion: Split stomas are a viable option in these high-risk patients. Good survival and nutritional outcomes are achievable, however this approach requires confidence in proximal stoma and safe PN management of Type II IF patients. Disclosure of interest: None Declared.